Retroactivity and legitimate expectation in the UK Administrative Law - Phillips Letelier, Jaime (Revista de Derecho Público: Teoría y método, 2023)
Both the doctrines of non-retroactivity and legitimate expectation find their normative foundation on the idea that legal norms and administrative decisions should be stable and predictable, thus allowing individual planning. This is problematic because the protection of individual planning does not fully explain the prohibiting sense often infused in the non-retroactivity principle and the different degrees in which retroactivity takes place. Also, the extension of this principle to genuine legitimate expectation cases may in unduly and excessive protection to individuals from law or policy changes. Thus, this papers proposes a new normative foundation for the non-retroactivity principle around the idea of finality in order to explain its prohibiting sense and to develop the understanding that retroactivity happens in degrees. Finally, this proposal will allow to make better sense of the legitimate expectation case law and the justification of compensation for damages caused by detrimental reliance.